Periodo intergenésico corto como factor de riesgo para el desarrollo de preeclampsia en gestantes - Huamán Florián, Jhohan Miguel (2018)
The intergenic interval is a determining factor of maternal and fetal morbidity and mortality. It has social, economic and demographic importance. Both the short intergenic period (24 months) and the long intergenic period (60 months) have been involved in adverse effects. Through this investigation, it is expected to find the relationship of the short intergenic interval as a risk factor for the development of preeclampsia. Objective: To determine if the short intergenic interval is a risk factor for the development of preeclampsia in pregnant women. Material and methods: An analytical, observational, case-control study was conducted in the Gynecology-Obstetrics Service of the Teaching Regional Hospital of Trujillo during the period January 2009 - December 2015, which evaluated 96 puerperal women, in which 48 cases were compared. , with 48 controls, to which the short intergenic period was measured. Results: No significant association was found between the variables studied. The frequency of short intergenic period in pregnant women with preeclampsia was 31%, while in pregnant women without preeclampsia it was 29%. Conclusion: The short intergenic period is not a risk factor associated with preeclampsia